MODEL KERANGKA KERJA SIKLUS BIMBINGAN DAN KONSELING ISLAM DI PESANTREN SEBAGAI UPAYA MENGATASI HAMBATAN BELAJAR SANTRI - Sudharno Dwi Yuwono (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2023)
The Islamic guidance and counseling program is needed to assist students with learning problems. The previous studies have shown guidance and counseling service strategies that can be used to help, but it’s still partial and not systematic. There needs to be a framework that can be a reference for developing counseling programs in Islamic boarding schools. This research uses a literature study method with content analysis. This research has produced a cycle framework model as a framework model in developing the Islamic guidance and counseling program at Pondok Pesantren.